PERTANGGUNG JAWABAN PIDANA TERHADAP PELAKU PENGGELAPAN DENGAN MENGGUNAKAN JABATAN MENURUT PASAL 374 KUHP DALAM PENDEKATAN TEORI PEMIDANAAN (Analisis Putusan Pengadilan Negeri Jakarta Selatan Nomor 1316/Pid.B/2017/PN.Jkt.Sel) - Miftakul Muntaha; Kartono Kartono (Program Studi Hukum Universitas Pamulang, 2020)
The crime that is rife and continues to grow until now is a crime against property. One crime that is a crime against property is a crime of embezzlement. Crimes of embezzlement are regulated in book II of the Criminal Law Act in Articles 372 - 377 KUHP which is a crime that often occurs in various layers of the lower layers of society, abuse of trust that dominates as the main element of this crime. Embezzlement has different types, one of which is embezzlement by occupation is a community disease that is closely related to crime, which in its historical process from generation to generation turns out that the crime is a crime that harms others and or the agency where the offender works. Criminal acts against embezzlement by position must be different from ordinary embezzlement because there are incriminating elements in it as regulated in the Criminal Code. Judges' considerations and legal facts are an influential part in determining the sanction imposed in criminal proceedings.